Photosynthetic efficiency in FMO complex : a dynamical study using the lindblad and non-equilibrium greens functions frameworks (2024)
This work aimed to study the efficiency of the photosynthetic complex Fenna-Matthews Olso (FMO). For this purpose, the behavior of the average efficiency in the reduced FMO system (FMO- 123) was analyzed employing two formalisms: the Lindblad master equation, and the Green functions. First, the dynamics of the system were found with the Lindblad formalism, which allowed to establish the Dynamical Efficiency of the FMO-123, defined by the ratio between the output and input power, which presented a maximum peak for a value of 50 ps−1 of the dephasing rate (γdeph). Second, through the retarded Green’s function, the density of states, and the use of Parseval’s theorem, an analogous expression for the Dynamical Efficiency was defined in this formalism. It has also a maximum for a value of 1.8 meV of the coupling of FMO with the reservoirs (Γ). From the two results obtained, it stands out how the calculation of the Dynamical Efficiency takes into account the dynamics reflected in the input power at site 1, different from how the efficiency of FMO has been treated in previous studies, providing a more complete understanding of the system behavior. On the other hand, the use of the Lindblad formalism indicated that the high efficiency of this complex is achieved by the environment-assisted quantum transport (ENAQT) regime. This could show that the efficiency can be maximum for a certain value of the dephasing rate, i.e. of the support from the environment, regardless of whether this support leads to the presence of long-lived coherences in the system. As a perspective, we plan to use both formalisms again to study the excitonic current of FMO.